The meanest doll in the world / 2. - Martin, Ann M., 1955- (The doll people, 2005)
Annabelle and Tiffany, dolls who are best friends living in the Palmer house, have an adventure when they hide in Kate Palmer's backpack, are carried to school, mistakenly go to another house, and try to stop Princess Mimi, a doll who threatens all dollkind.